The Level of Preference and Nutritional Content of Belitung Taro Flour Biscuits (Xanthosoma sagittifolium L. Schott) with the Addition of Shark Catfish Flour - Putri, Salsa Ayu Andrea; Anugrah, Riva Mustika (Universitas Pendidikan Indonesia, 2024)
Background: Biscuits are a snack made from wheat flour. Modification of processed biscuits is by replacing wheat flour with Belitung taro flour with the addition of patin flour which aims to increase the protein content. The objective of this research describe the level of preference and nutritional content of Belitung taro flour biscuits (Xanthosoma sagittifolium L. Schott) with the addition of patin flour (Pangasius sp.).Research Methods: Experimental Study using 3 formulations of Belitung taro flour: patin flour, F1 = 80%: 20%, F2 = 70%: 30%, and F3 = 60%: 40%. The preference level test was carried out on 25 moderately trained panelists. Analysis of the preference level test used descriptive tests. Analysis of nutritional content in the form of protein using micro-kjehdal, fat using the Soxhlet method, carbohydrates using the method by difference, and water content using gravimetric.Research Result: The biscuit formulation with the highest level of preference was F2 with descriptive analysis results of 71.45% using a comparison of 70% Belitung taro flour and 30% patin flour. The nutritional content of biscuits per 100 grams is 450.6 kcal energy, 8.93 grams protein, 14.5 grams fat, 70.9 grams carbohydrates and 2.1% water content.Conclusion: The best biscuit formulation is F2 with a composition of 70 grams of Belitung taro flour and 30 grams of patin flour. The energy content of biscuits can meet 16.68% of the daily energy needs of children aged 1-3 years.